RANCANG BANGUN SISTEM TOKEN PULSA PENGGUNAAN AIR PRA-BAYAR METODE ENKRIPSI TRANSPOSISI DAN DEKRIPSI ALJABAR BOOLEAN - Rima Ayuning Ratri; Kusworo Adi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Water supply company is currently still using analog counter system to determine the volume of water that has been used by customer. After officers did manually recording then customer make a payment according the volume of water used. This system raises many problems include, payment arrears, the recording of water unsuitable and customers can’t to arranged the water. So, we needs a system that can to overcome it all. Water counters prepaid system uses token that contains important information such as the customer's ID, date of purchase and nominal credit tokens. To maintain secrecy and make disposable token, cryptographic process carried out by the method of transposition. To use the token decryption process is done by microcontroller PIC16F877. Decryption process performed by implementing the Boolean Algebra. Results from this research are created of water counters prepaid system by using a token and has 100% success rate. Water counter prepaid system are expected to reduces cheating on analog water counter and customers can arrange the water needs.Keywords: Water prepaid system, Token, Cryptographic, Transposition, PIC16F877A.